PKM Pelatihan Strategi Pengembangan Bauran Pemasaran Untuk Peningkatan Omzet UMKM - Yulia Nurendah; Ani Mekaniwati; Dwi Maulina (Jurnal Abdimas Dedikasi Kesatuan, 2021)
The marketing aspect plays a very important role. Products that are preferred by consumers, setting the right price, choosing the right location and distribution channels, and the right promotion will be able to increase business performance in terms of marketing and turnover earned. Marketing Mix Development Strategy Training for Increasing MSME Turnover aims to 1) Increase knowledge and understanding regarding product development in terms of variant, packaging, size, brand and quality. 2) Increase knowledge and understanding regarding product pricing that attracts consumers. 3) Increase knowledge and understanding regarding the development of distribution channels and selection of appropriate business locations. 4) Increase knowledge and understanding regarding the development of promotional strategies To carry out these activities, several training methods are used, namely: Lecture Method, Question and Answer Method, and Simulation Method. This simulation method is very important given to the training participants to provide the opportunity to practice the training material obtained. The hope is that the training participants will really master the training material received, know their level of ability to apply entrepreneurial activities technically and then identify the difficulties (if they still exist) to be solved later. The evaluation of the success of this training shows the following data: as many as 81% of MSME participants / players can understand well the activities of implementing the marketing mix development training, 76% of MSME participants / players are able to practice marketing mix development, As many as 78% of MSME participants / players are willing to socialize their abilities development of the marketing mix to colleagues. Taking into account these data, it can be concluded that the training success indicators that have been set at the beginning get optimal results and reach the target. Key words: marketing mix